Transcriptome Analysis Provides Insights into the Safe Overwintering of Local Peach Flower Buds - Ruxuan Niu; Yongjuan Cheng; Falin Wang; Yiwen Zhang; Chenbing Wang (Current Issues in Molecular Biology, 2024)
During the dormant period of peach trees in winter, flower buds exhibit weak cold resistance and are susceptible to freezing at low temperatures. Understanding the physiological and molecular mechanisms underlying the response of local peach buds to low-temperature adversity is crucial for ensuring normal flowering, fruiting, and yield. In this study, the experimental materials included the conventional cultivar ‘Xia cui’ (XC) and the cold-resistant local resources ‘Ding jiaba’ (DJB) peach buds. The antioxidant enzyme activity, levels of malondialdehyde (MDA), proline (Pro), and hydrogen peroxide content (H2O2) were determined in peach buds at different dormancy periods. Transcriptome sequencing was performed at three dormancy stages: the dormancy entry stage (FD), deep dormancy release stage (MD), and dormancy release stage (RD). Additionally, transcriptome sequencing was conducted to analyze gene expression profiles during these stages. Our findings revealed that compared with XC cultivars, DJB peach buds exhibited decreased MDA and H2O2 contents but increased superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) activities as well as Pro content during the dormancy period. These findings suggest that cold-resistant cultivars possess significantly stronger antioxidant capacity than conventional cultivars under low-temperature stress. A total of 10,168 differential genes were annotated through transcriptome sequencing. Among them, 4975 were up-regulated while 5193 were down-regulated. The differentially expressed genes associated with low-temperature response in peach buds are primarily enriched in plant hormone signal transduction pathway and phenylpropane synthesis pathway. Key differentially expressed genes related to cold resistance include ARF2, GH3, and SAPK2, and differentially expressed transcription factors mainly belong to the AP2/ERF-ERF, bHLH, and C2H2 families. This study provides a theoretical foundation for understanding the key genes involved.